2018
DOI: 10.1093/europace/euy155
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic interference in cardiac electronic implants caused by novel electrical appliances emitting electromagnetic fields in the intermediate frequency range: a systematic review

Abstract: Electromagnetic fields (EMF) in the intermediate frequency (IF) range are generated by many novel electrical appliances, including electric vehicles, radiofrequency identification systems, induction hobs, or energy supply systems, such as wireless charging systems. The aim of this systematic review is to evaluate whether cardiovascular implantable electronic devices (CIEDs) are susceptible to electromagnetic interference (EMI) in the IF range (1 kHz-1 MHz). Additionally, we discuss the advantages and disadvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 67 publications
0
18
0
6
Order By: Relevance
“…A systematic review by Driessen et al showed that electromagnetic fields in the intermediate frequency range (1 kHz to 1 MHz) may interfere with CIEDs depending on the duration of exposure and device or lead characteristics 29 . Interference occurs when electromagnetic waves which are in constant phase to each other overlap precisely 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Driessen et al showed that electromagnetic fields in the intermediate frequency range (1 kHz to 1 MHz) may interfere with CIEDs depending on the duration of exposure and device or lead characteristics 29 . Interference occurs when electromagnetic waves which are in constant phase to each other overlap precisely 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies detected severe EMI with altered CIED function when the sensitivity of the CIEDs was lowered and at the setting of a unipolar sensing configuration 25 . In fact, the risk of EMI with CIEDs could be reduced by programming the sensitivity settings and altering the lead sensing configuration from a unipolar to bipolar model 31 . The sensitivity should be set at a high value, which could both ensure an appropriate sensing of intrinsic cardiac signals and avoid oversensing in the atrial or ventricular channel.…”
Section: Discussionmentioning
confidence: 99%
“…Implantable medical devices (IMDs) are an example of a safety-critical system where external electromagnetic interference (EMI) can cause physical harm to people. As a result, there is extensive research on the EMI behavior of various IMDs [82]- [94]. Some of these works have even pinpointed the properties of "non-linear circuit elements" in pacemakers as the culprits for demodulating RF signals produced by cell phones [86], [95].…”
Section: Electromagnetic Transmissionsmentioning
confidence: 99%